PERFORMANCE ANALYSIS OF THE EM100 CONTROLLER IN AN ELECTRIC MOTORCYCLE CONVERSION PROTOTYPE - Setiawan, Aries F. Setiawan; Sriyono; Ramdhani (Pengelolaan Penerbitan Publikasi Ilmiah (P3I) Politeknik Negeri Madiun, 2025)
This study aims to test the performance of the Votol EM100 controller on a converted electric bicycle with a battery capacity of 72 volts 15Ah paired with a mid-drive BLDC motor with a power of 4KW. This study focuses on testing to obtain peak results for torque, speed (top speed), engine rotation, and horsepower (HP) that can be produced by the Votol EM100 controller. The testing was conducted using a BRT 50 LE motor dyno test tool. The data obtained from the testing included a peak torque of 25.83 Nm at 4,520 RPM, a peak speed (top speed) of 97.94 km/h with a duration of 18.19 seconds, and a peak horsepower (HP) of 14.59 horsepower (HP) with a duration of 11.31 seconds.